The Influence of Consumer Reviews, Discounts, Payments Through Digital Banking and Peer Influence on Online Shopping Decisions on the Shopee Platform: on FEBI UIN Sumatera Utara Students - Dina Aulia; Nursantri Yanti; Muhammad Lathief Ilhamy Nasution (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the influence of Consumer Reviews, Discounts, Payments via Digital Banking, and Peer Influence on Purchasing Decisions of FEBI UIN Sumatera Utara students on the Shopee platform. The study used a quantitative approach with the SEM-PLS method through SmartPLS 4 and data obtained from distributing questionnaires to 100 students of the class of 2022. The results showed that all variables had a positive and significant effect on purchasing decisions, both partially and simultaneously, with an R-Square value of 0.809. Payments via Digital Banking were the most dominant factor, followed by Consumer Reviews, Peer Influence, and Discounts. These findings indicate that students' online shopping decisions are influenced by a combination of informational, economic, technological, and social factors within the e-commerce ecosystem